2021
DOI: 10.48550/arxiv.2111.11417
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quasimaps to moduli spaces of sheaves

Abstract: We develop the theory of quasimaps to moduli spaces of stable sheaves on a surface. Under some natural assumptions we prove that the moduli spaces of quasimaps are proper and carry a perfect obstruction theory. Moreover, the moduli spaces of quasimaps are naturally isomorphic to certain relative moduli spaces of sheaves. Using the theory of entangled tails we establish the wall-crossing formulae which relate Donaldson-Thomas theory of threefolds of the type Surface×Curve to Gromov-Witten theory of moduli space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…In the last section we saw the relationship between the theories (i) and (ii). 5 In this section we review the wall-crossing formula between (ii) and (iii) obtained by Nesterov [42] using the theory of quasimaps. Our discussion follows the survey paper [44].…”
Section: Nesterov's Hilb/pt Wall-crossingmentioning
confidence: 99%
“…In the last section we saw the relationship between the theories (i) and (ii). 5 In this section we review the wall-crossing formula between (ii) and (iii) obtained by Nesterov [42] using the theory of quasimaps. Our discussion follows the survey paper [44].…”
Section: Nesterov's Hilb/pt Wall-crossingmentioning
confidence: 99%
“…By Lemma 4.2 the series ( 58) is a Laurent polynomial in p. Proof. Denis Nesterov in [67,68] showed that the left hand side is equal to a partition function of relative Pandharipande-Thomas invariants of (S × C, S z ), see in particular [68,Cor.4.5]. The statement follows then from the GW/PT correspondence for (S × C, S z ) proven in [72, Thm.1.2] whenever β is primitive.…”
Section: Hilb/gw Correspondencementioning
confidence: 89%
“…The cycle Z S [n] (p, q) also appears naturally in the Pandharipande-Thomas theory of the relative threefold (S × P 1 , S 0,∞ ). Indeed, by Nesterov's quasi-map wallcrossing [67,68] and the computation of the wall-crossing term in [81] one has…”
Section: ∆(Q)mentioning
confidence: 99%
See 2 more Smart Citations